PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBASIS STEAM TERHADAP LITERASI SAINS DAN HASIL BELAJAR SISWA SD - Kiky Deka Ages Novita; Farida Nur Kumala; Arnelia Dwi Yasa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teachers must incorporate four essential elements in the learning process: the use of models, methods, approaches, and media. This research was motivated by the observation that many educators rely solely on traditional methods such as lectures, question-and-answer sessions, and assignments, without utilizing appropriate learning models and media. As a result, students often experience low science literacy and poor learning outcomes, especially in topics such as plant structure and function. This study aims to examine the effect of the STEAM-based discovery learning model on science literacy and learning outcomes of fourth-grade students at SDN Gadang 4. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent pre-test post-test control group. The subjects consisted of two groups: an experimental class and a control class, each comprising 27 students. Research instruments included science literacy and achievement tests administered before and after the treatment. The test items were developed based on specific indicators. Validity was tested using the product moment pearson formula, and reliability was measured using cronbach's alpha. Data analysis included calculating the normalized gain (n-gain), testing data distribution with the shapiro-wilk test, testing variance homogeneity with levene’s test, and examining group differences using independent samples t-test and welch’s t-test. The results indicated that the experimental class achieved significantly higher post-test scores than the control class. This finding demonstrates that the STEAM-based discovery learning model has a significant positive effect on improving students' science literacy and learning outcomes in elementary science education.